Arts-driven sustainability and sustainably driven arts. Issue 1 (1st July 2018) - Garrett, Ian
With the founding of the National Endowment for the Arts, Lyndon Johnson stated that '[...] we reveal to ourselves and to others the inner vision which guides us as a nation. And where there is no vision, the people perish'. Today, we are facing the largest existential threat to human civilization as a result of human-made climate change. Research into the three dimensions of sustainable development articulated by the UN's Brundtland Commission reveals that the arts have positive impacts in each area. The arts are drivers of social cohesion, and build our individual and shared identities. The arts contribute to the economy significantly above the rates of public and private funding allocated to them, especially at a local level. And, by congregating people together and sharing ideas have real and significant potential positive environmental impacts. These impacts offer evidence that society can become more sustainable with arts at the centre.